Perbedaan Motivasi Wanita PUS Usia 35-49 Tahun untuk Menggunakan Implant Sebelum dan Setelah Diberi Penyuluhan di Dusun Mojolegi Desa Bendo Kec. Pare. - Triatmi Andri Yanuarini; Susanti Pratamaningtyas; Rika Aprilia Susanti (coba, 2015)
Women who have age 35 these group will get increased morbidity and mortality experience if they pregnant. Implant is one method of effective an safety long-term contraception. Bendo Health Center have the lowest acceptor implants in Kediri that is 0%. The purpose of this research to know the difference motivation of childbearing age couples women in age 35-49 years to use implant before and after giving information. The design used a pre-experiment design with one group pre-test post-test design, the population was all childbearing age couples women in age 35-49 years at Mojolegi Hamlet Bendo Village Pare District who have children, not use contraception or still use non-Long Term contraception Method which total 72 people. The samplehave a lot 61 people according to inclusion and exclusion criteria. The sample removal technique used simple random sampling. The result of this research, from 61 respondents get average of respondent motivation before give information is 65 and after give information is 69, show that respondent’s motivation get increase after got information. And after going through the data analysis it was found z calculate > z table, so in this case have difference motivation of childbearing age couples women in age 35-49 years to use implants before and after giving information. Keywords: Counseling, Motivation, Implants